Perencanaan Kantor Dakwah: Adaptasi Framework Manajemen pada Konteks Organisasi Dakwah - Sumardianto, Erdin (STID Al-Hadid, 2024)
Planning is one of the most crucial management functions for a da'wah organization, including in planning its office. However, conventional planning frameworks are based on the realities of business organizations, which have very different characteristics from da'wah organizations, particularly in managing offices as the base of their activities. Therefore, an adaptation of the planning framework is needed to be compatible with the management needs of a da'wah office. This study aims to adapt the conventional planning framework so it can be applied in planning for da'wah offices. A qualitative approach is used, with a conceptual study and theory adaptation approach. Data is sourced from literature on planning concepts and da'wah office variables. The results of the framework adaptation are: First, the formulation of goals/objectives must align with the supporting role of the da'wah office in achieving the broader goals of the da'wah organization. Second, the mapping of strategic factors for the da'wah office should match its more specific characteristics compared to the broader strategic factors of the organization, covering both physical and non-physical aspects of the office from internal and external environments. Third, the formulation of strategies and implementation plans for the da'wah office should focus on organizing both physical (Buildings, rooms, and facilities) and non-physical aspects of the da'wah office (Organizational culture, instilling da'wah values, and fostering an Islamic environment).